Fuel Subsidies in Ecuador: A Computable General Equilibrium Model for Targeting Evaluation - Cristhian Montenegro-Casa; José Ramírez-Álvarez (Latin American Research Review)
Fuel subsidies have been an enduring policy in Ecuador’s political and economic history. Given their lack of targeting and high opportunity cost, they have been amply criticized. As of 2017, the Ecuadorian government started a budget consolidation plan that so far has involved seven reforms to subsidies policy in less than seven years. In late 2019, in response to social unrest motivated by a temporal elimination of fuel subsidies, the government pledged to study new targeting mechanisms for this policy to mitigate the impact on the most vulnerable sectors. This work seeks to contribute to that effort by evaluating the macroeconomic effects of these subsidies and serving as a guideline for targeting. A computable general equilibrium model is used to assess counterfactual scenarios. The results suggest that by implementing progressiveness and productive linkage criteria, targeting household final consumption and intermediate consumption is a feasible way to reduce the reforms’ negative effects.